Math trigonometry

posted by .

8sin^2theta+10 sin theta cos theta =3cos^2 theta=0 then general solution for theta is

  • Math trigonometry -

    Assuming you meant

    8sin^2θ+10 sinθ cosθ+3cos^2θ = 0
    (2sinθ+cosθ)(4sinθ+3cosθ) = 0

    see what you can do with that.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra II

    Which of the following expressions are not equal to 1?
  2. Calculus

    I wanted to confirm that I solved these problems correctly (we had to convert the polar curves to Cartesian equations). 1.rcos(theta)=1 x=1 2.r=2*sin(theta)+2*cos(theta) r^2=2rsin(theta)+2rcos(theta) x^2+y^2=2y+2x (a little unsure …
  3. trigonometry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  4. trigonometry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  5. Algebra II

    Multiple Choice Which expression is NOT equivalent to 1?
  6. Trigonometry

    find all values of theta in the interval 0<theta<360 that satisfy the equation 3cos 2theta + 2 sin theta+1=0
  7. math(Trigonometry)

    sin 2 theta + cos theta = 0 so, we use sin 2 theta = 2 sin theta cos theta right?
  8. Mathamatics

    Solve the following trigonometry identities. a) 1-cos2(theta) = sin(theta)cos(theta)/cot(theta) b) (1-cos2(theta))(1-tan2(theta))=sin2(theta)-2sin4(theta)/1-sin2(theta) *its supposed to be cos to the power of two, sin to the power …
  9. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …
  10. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …

More Similar Questions